How effective is the European neighbourhood policy as a mechanism for transposing the European Union's democratic values in the south Caucasus? - Ghazaryan, Narine (2010)
The central focus of the research conducted is the European Neighbourhood Policy aimed at developing the relations of the European Union with its neighbours in the East and South. The European Neighbourhood Policy has an extensive nature: it covers a wide-stretching geopolitical area including sixteen countries. The policy is also extensive in terms of its all-encompassing substance: it envisages cooperation between the parties on issues ranging from trade to border control. The research question contextualises the policy in geographical and substantive terms. The region of the South Caucasus was chosen to limit the research question to certain geographical framework. This is motivated by the complexities inherent in this geographical area. The nominal region of South Caucasus comprises Georgia, Armenia and Azerbaijan. The peculiarities of these states derive from complexities inherent within these states, complexities between the states, as well as between various geopolitical actors whose interests come across here. In substantive terms the research question is limited to the framework of promoting the European Union's democratic values. The main questions addressed in this relation are: what the Union's democratic values are and whether the policy in question offers sufficient mechanisms for their transposition to the South Caucasian countries. For this purposes the instruments and methodologies of the policy have been analysed. The democratic values of the Union have also been considered. Within this narrative, a comparative analysis of the process of the ENP implementation in three states has been undertaken to evaluate its effectiveness in promoting the democratic values of the European Union. The research is finalised with a summary of findings.